2019
DOI: 10.3390/genes10090650
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Purification of NF1 Protein–Protein Interactors Identifies Keratins and Neurofibromin Itself as Binding Partners

Abstract: Neurofibromatosis Type 1 (NF1) is caused by pathogenic variants in the NF1 gene encoding neurofibromin. Definition of NF1 protein–protein interactions (PPIs) has been difficult and lacks replication, making it challenging to define binding partners that modulate its function. We created a novel tandem affinity purification (TAP) tag cloned in frame to the 3’ end of the full-length murine Nf1 cDNA (mNf1). We show that this cDNA is functional and expresses neurofibromin, His-Tag, and can correct p-ERK/ERK ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
(91 reference statements)
1
7
0
1
Order By: Relevance
“…Hence, this region (exons 18-21) may be critical and should not be targeted for exon skipping. These data are compatible with the recent finding that neurofibromin forms a dimer/oligomer (24,25). While regions critical for dimerization have not yet been reported, it is possible that they overlap with these critical exons.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, this region (exons 18-21) may be critical and should not be targeted for exon skipping. These data are compatible with the recent finding that neurofibromin forms a dimer/oligomer (24,25). While regions critical for dimerization have not yet been reported, it is possible that they overlap with these critical exons.…”
Section: Discussionsupporting
confidence: 92%
“…A published report noted that human neurofibromin eluted from size-exclusion chromatography during purification as an apparent dimer (22), and other studies have proposed that multimerization could potentially explain dominant-negative effects of heterozygous truncation mutations of NF1 in patients (23). A recent paper published during the preparation of this manuscript demonstrated that tagged murine neurofibromin could co-IP human neurofibromin in HEK293 cell lines, suggesting that these highly-homologous proteins from the two species (Ͼ98% identity) could form dimers as well (24).…”
Section: Discussionmentioning
confidence: 76%
“…An additional complexity to NF1 interactions is its dimerization activity (Figure 1, left) (Carnes, Kesterson, Korf, Mobley, & Wallis, 2019;Sherekar et al, 2019). While the mechanistic significance has yet to be determined, dimerization provides a potential explanation for the phenotypes observed with many NF1 disease variants.…”
Section: Introductionmentioning
confidence: 99%